Luodi Shenggen in West San Gabriel Valley: practicing home amidst migrant precarity in US American neighborhoods - Lin, Shasha; Gerhard, Ulrike (Population, space and place, 2026)
This paper contributes to the theoretical debates on migrant dwelling and urban belonging in an era of heightened global mobility by exploring the multidimensional, multi-scalar and mobile concepts of home among newly arrived, undocumented Chinese immigrants in the West San Gabriel Valley, Los Angeles. Rather than portraying home as a romanticized place that has been left, we employ a mobile concept that bridges the question of where and what home is to how migrants practice home in new urban environments. This helps to connect the material, relational, and emotional meanings of home, showing how new immigrants assert agency through homemaking practices amidst three specific types of precarity: housing, work and legal. We suggest that the neighborhood emerges as a crucial site, where migrants cultivate familiarity, build social ties, and assert agency through daily routines. Based on 31 interviews and 5 months of participant observation, our study also addresses a critical gap in home in migration literature by focusing on undocumented Chinese immigrants, a group often obscured by the model minority narrative.